2013
DOI: 10.4067/s0034-98872013000900007
|View full text |Cite
|
Sign up to set email alerts
|

Efecto in vitro de los terpenos lupeol y casearina G sobre células sanguíneas y tumorales

Abstract: In vitro effect of lupeol and casearin G on peripheral blood mononuclear and tumor cells GI 50 = 13.3 μM; GI 50 = 11.8 μM; LC 50 = 49.4 μM), as well as a hemolytic effect (≥ 182 μM). Conclusions: These observations indicate that lupeol and casearin G might be useful compounds in the preparation of antiinflammatory drugs, whereas casearin G might be useful in the elaboration of antitumor drugs. (Rev Med Chile 2013; 141: 1150-1157.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The results shown indicate that lupeol induces apoptosis at 72 h after treatment (Figure ) with respect to control cells. Similar reports have been reported that LP can interact with multiple molecules, affecting and modulating the inflammatory process and the response to cellular stress; in addition, it has shown low cytotoxicity in healthy cells and acts synergistically when used in combined therapies; however, the exposure of this liposoluble molecule can promote the interaction with constituent molecules of the cell membrane, thus leading to apoptosis induction …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The results shown indicate that lupeol induces apoptosis at 72 h after treatment (Figure ) with respect to control cells. Similar reports have been reported that LP can interact with multiple molecules, affecting and modulating the inflammatory process and the response to cellular stress; in addition, it has shown low cytotoxicity in healthy cells and acts synergistically when used in combined therapies; however, the exposure of this liposoluble molecule can promote the interaction with constituent molecules of the cell membrane, thus leading to apoptosis induction …”
Section: Resultssupporting
confidence: 76%
“…Similar reports have been reported that LP can interact with multiple molecules, affecting and modulating the inflammatory process and the response to cellular stress; in addition, it has shown low cytotoxicity in healthy cells and acts synergistically when used in combined therapies; however, the exposure of this liposoluble molecule can promote the interaction with constituent molecules of the cell membrane, thus leading to apoptosis induction. 33 In the same way, mangiferin-loaded ZnO particles (ZnO A -MG) induce apoptosis; in this sense, ZnO promotes ROS production, which has been associated with the induction of apoptosis by the extrinsic pathway, through the activation of procaspase 8. 34 Regarding mangiferin not inducing apoptosis, as can be seen in Figure 2, with respect to control cells, these results are in line with studies carried out by our research group on healthy BEAS-2B cell lines, where this phytochemical did not show cytotoxicity; 23 however, it does promote apoptosis in cancer cells (HEPG2).…”
Section: Resultsmentioning
confidence: 99%
“…Considering NO is a free radical, it is extremely reactive and causes damage to proteins and DNA. Thus, NO has antimicrobial and antitumour potential and is also an antiviral agent . Production of nitrite as an indicator of NO synthesis was measured in the culture supernatant of macrophages, and LPS was used as an inducer of nitric oxide production in the positive control group.…”
Section: Discussionmentioning
confidence: 99%
“…Culture of the colon cancer cell line was performed using a modification of the methodology described by Díaz et al, (2013) and Dupuy et al, (2013). For this, the cells in suspension were maintained in culture flasks and Petri dishes containing Eagle-Dulbecco's modified medium (DMEM) supplemented with 10% heat-inactivated fetal bovine serum, penicillin (100 U mL -1 ) and streptomycin (0.1 mg mL -1 ).…”
Section: Cell Culturementioning
confidence: 99%